Comparative study of coronal sealing ability using root cross sections method - Marković Dejan; Živojinović Vesna; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2007)
Objective: An in vitro comparison of coronal microleakage of three root canal sealers was performed using the dye leakage method. Methodology: Ninety-eight single-rooted human teeth were instrumented and randomly allocated to two groups. In the first group, root canals were treated with EDTA to remove the smear layer. The roots in both groups were obturated using laterally condensed gutta-percha and Sealapex, AH-26 or Ketac-Endo as the sealer. The teeth were suspended in 1% methylene blue dye for 6 days. The teeth were then rinsed, sectioned perpendicular to the long axis and evaluated for coronal dye penetration. Results: In general, Ketac-Endo root canal sealer showed greater dye penetration than Sealapex and AH-26. A statistically significant difference in the coronal penetration of the dye was found in the group with intact smear layer. Conclusion: Highly significant differences between AH-26 and Ketac-Endo (p < 0.001) and Sealapex and Ketac Endo (p < 0.001) were found.